Análise de corrosão dos aços inoxidáveis AISI 304 e AISI 316L em solução de água do mar artifícial - Frutuoso, Francisca Geidilany Saraiva de Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
The corrosive process generates many expenses in the mechanics world and there is a growing demand for corrosion resistant material, so the knowledge of corrosive behavior of various materials becomes essential. This research aims to characterize the behavior of austenitic stainless steels AISI 316L and AISI 304 in artificial sea water solution. The bibliographic study was aimed at emphasizing the characteristics and particularities of the materials, methods and tests used. Among the obtained results we can mention characterization of the material by chemical composition and x-ray diffraction, metallographic study, calculation of the corrosion rate and mass loss rate, after exposure of the materials in the medium for a predetermined time, electrochemical spectroscopy electrochemical impedance and potentiodynamic polarization, as well as the measurement of pH and conductivity of the solution. With the comparison and analysis of the cited parameters it was concluded that AISI 304 and AISI 316L are not sensitive to the artificial sea water solution, however corrosion occurs and is predominantly in the pites form. AISI 316L steel proved to be significantly more resistant to corrosion than AISI 304.
Monografia
Keywords: Aço inoxidável; Corrosão; Ensaios eletroquímicos; Meio salino; Resistência à corrosão; Stainless steel; Corrosion; Electrochemical tests; Saline ambient; Resistance to corrosion; ENGENHARIAS::ENGENHARIA MECANICA